Long‐term follow‐up of surgical outcomes for patients with Wilms tumor and neuroblastoma. Issue 17 (27th May 2021) - Cooke‐Barber, Jo; Scorletti, Federico; Rymeski, Beth; Eshelman‐Kent, Debra; Nagarajan, Rajaram; Burns, Karen; Jenkins, Todd; Dasgupta, Roshni
Abstract : BACKGROUND: There are minimal data on long‐term surgical outcomes of patients who have undergone resection for Wilms tumor (WT) and neuroblastoma (NB). METHODS: A retrospective review of patients in a long‐term survivor clinic between the years 1967 and 2016 in a pediatric tertiary care hospital (>5 years posttreatment) was performed. RESULTS: Eighty‐six survivors of WT and 86 survivors of NB who had ongoing follow‐up in the survivors' clinic were identified. The median age at diagnosis was 2.5 years (range, 0.4‐15.7 years) with a mean follow‐up of 22.3 years (±10.4 years) for WT. The median age at diagnosis for patients with NB was 0.9 years (range, 0.1‐8.6 months); mean follow‐up of 21.7 years (±7.9 years). Twelve patients with WT (14.0%) had at least 1 repeat laparotomy, 11.1% for bowel obstruction, at a median of 3 months from initial surgery. Twelve patients (14.0%) with NB required laparotomy and 8.1% for bowel obstruction, at a median of 12 years after initial surgery. The incidence of hypertension in patients with WT who had undergone nephrectomy was not outside of population norms. Patients who underwent thoracotomy for a NB have a higher incidence of scoliosis and Horner syndrome. CONCLUSIONS: Small bowel obstruction requiring laparotomy is significantly higher than the literature norms for both tumor patient populations and typically occurs in the early postoperative period for patients with WT and remotely in patients with NB. The long‐term surgical complications of patients who underwent resection for NB and WT clearly merit follow‐up and patient education within multidisciplinary long‐term survivorship clinics. Abstract : In this study, the long‐term surgical outcomes of patients who have survived Wilms tumor and neuroblastoma were examined. The rate of small bowel obstruction requiring laparotomy was higher than population norms.